2013
DOI: 10.1016/j.bbamcr.2012.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Signaling the mitochondrial unfolded protein response

Abstract: Mitochondria are compartmentalized organelles essential for numerous cellular functions including ATP generation, iron-sulfur cluster biogenesis, nucleotide and amino acid metabolism as well as apoptosis. To promote biogenesis and proper function, mitochondria have a dedicated repertoire of molecular chaperones to facilitate protein folding and quality control proteases to degrade those proteins that fail to fold correctly. Mitochondrial protein folding is challenged by the complex organelle architecture, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
288
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(296 citation statements)
references
References 102 publications
(149 reference statements)
5
288
1
2
Order By: Relevance
“…The UPR mt acts similarly to the UPR of the endoplasmic reticulum (19). While the UPR of the endoplasmic reticulum was the first to be identified, the activation of the UPR mt has only recently begun to be appreciated (20)(21)(22)(23)(24) and has yet to be elucidated. Moreover, its relation to cancer has not been established.…”
mentioning
confidence: 99%
“…The UPR mt acts similarly to the UPR of the endoplasmic reticulum (19). While the UPR of the endoplasmic reticulum was the first to be identified, the activation of the UPR mt has only recently begun to be appreciated (20)(21)(22)(23)(24) and has yet to be elucidated. Moreover, its relation to cancer has not been established.…”
mentioning
confidence: 99%
“…We also examined the levels of eIF2α and AKT phosphorylation that are considered as the downstream signal transducers of the matrix and IMS unfolded protein stresses, 42,43 respectively. We found that both eIF2α and AKTwere hyperphosphorylated in dYME1L del flies (Figure 6b), further confirming the elevated UPR mt .…”
Section: Resultsmentioning
confidence: 99%
“…While UPR mt was first discovered in mammals (Martinus et al, 1996), the molecular mechanism involved has been more extensively studied in the model organism Caenorhabditis elegans (Pellegrino et al, 2013). Worm strains, expressing a GFP reporter fused to promoters of the mitochondrial chaperones HSP-6 and HSP-60 (homologs of mammalian mtHSP70 and HSP60, respectively), were used to evaluate the activation of the UPR mt pathway.…”
Section: Proteostasis In Mitochondria the Upr Mtmentioning
confidence: 99%